Religiosity and psychological resilience in patients with schizophrenia and bipolar disorder: an international cross‐sectional study. (15th November 2017) - Mizuno, Y.; Hofer, A.; Frajo‐Apor, B.; Wartelsteiner, F.; Kemmler, G.; Pardeller, S.; Suzuki, T.; Mimura, M.; Fleischhacker, W. W.; Uchida, H.
Abstract : Objective: The impact of religious/spiritual activities on clinical outcomes in patients with serious mental illnesses remains controversial, which was addressed in this international cross‐sectional study. Method: Three‐hundred sixty‐nine subjects were recruited from Austria ( n = 189) and Japan ( n = 180), consisting of 112 outpatients with paranoid schizophrenia, 120 with bipolar I disorder (DSM‐IV), and 137 healthy controls. Religiosity was assessed in terms of attendance and importance of religious/spiritual activities, while resilience was assessed using the 25‐item Resilience Scale. General linear models were used to test whether higher religiosity will be associated with higher resilience, higher social functioning, and lower psychopathology. The association between levels of spiritual well‐being and resilience was also examined. Results: Attendance of religious services ( F [4, 365] = 0.827, P = 0.509) and importance of religion/spirituality ( F [3, 365] = 1.513, P = 0.211) did not show significant associations with resilience. Regarding clinical measures, a modest association between higher importance of religion/spirituality and residual manic symptoms was observed in bipolar patients ( F [3, 118] = 3.120, P = 0.029). In contrast to the findings regarding religiosity, spiritual well‐being showed a strong positive correlation with resilience ( r = 0.584, P < 0.001). Conclusion: The protective effect of religiosity in terms of resilience, social functioning, and psychopathology was not evident in our sample. Spiritual well‐being appears more relevant to resilience than religiosity.